Letramento em saúde e usabilidade de tecnologia digital para prevenção de problemas na amamentação - ROCHA NETA, Agostinha Pereira (2021)
SOS Mama is an mHealth technology developed with the purpose of helping puerperal women who experience difficulties in breastfeeding. In addition to building and validating the application, it is necessary to ensure that the technology is appropriate to the level of health literacy and usability for understanding and acceptance by the target audience. The objective was to evaluate the health literacy and usability of the SOS Mama application on the prevention of breastfeeding problems. Methodological research with validation study, conducted with postpartum mothers admitted to the Joint Nursing Unit of the Maternal and Child Unit of the University Hospital of UFMA. The collection was performed in April 2021, with application of the questionnaire with socio-demographic, obstetric, and breastfeeding variables, Health Literacy Scale (HLS - 14) and the System Usability Scale (SUS). The collected data were stored in a specific database, created in Microsoft Excel version 2016. The analyses were performed in the IBM SPSS 24 program with significance at 5%. The study was submitted for review to the Research Ethics Committee (REC) of the Federal University of Maranhão, which obtained a favorable opinion, according to opinion number 4,645,145. The research was carried out with 100 puerperal women, most of them aged between 18 and 25 years (53%), declared to be brown (68%), had no partner (54%) and lived in São Luís - MA (85%). As for education, they had more than eight years of schooling (84%), were employed (90.2%) and had income between one and four minimum wages (75%). As for obstetric characteristics, puerperal women had two or more pregnancies (67%), had six or more prenatal visits (65.6%), in the public (92.9%) and private (7%) networks, and 52% had a cesarean delivery. The majority received orientation on breastfeeding in the prenatal or maternity hospital (91%), however, they presented difficulties in their previous experience with breastfeeding (52.2%). Health literacy showed a median of 46 points (between 29 and 69 points) and 52% of postpartum women had low health literacy. The literacy classification was compared with socio-demographic, obstetric, and breastfeeding- related characteristics, and differences were observed (p>0.05) regarding education, number of pregnancies, and prenatal consultations. The Usability Test of the SOS Mama application, using the SUS questionnaire, obtained a score of 70.5, with a maximum score of 95 and a minimum of 45, thus confirming the validity of the application regarding usability and application.